2008
DOI: 10.1002/syn.20607
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptor mGlu2 and mGlu3 knockout striata are dopamine supersensitive, with elevated D2High receptors and marked supersensitivity to the dopamine agonist (+)PHNO

Abstract: The finding that the mGlu2/3 metabotropic glutamate receptor agonist, LY404039, improves clinical symptoms in schizophrenia warrants a search for a possible interaction between mGlu2/3 receptors and dopamine D2 receptors. Here, this topic is examined in striatal tissue of mice lacking either mGlu2 or mGlu3 receptor. Such mice are known to be behaviorally supersensitive to dopamine receptor agonists. Therefore, to determine the basis of this dopamine supersensitivity, the proportion of dopamine D2High receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…This possibility has also been supported by in vitro and in vivo experimental evidence in which group II mGluRs negatively modulated dopamine release in the limbic and cortical regions [5]. Seeman et al [32] revealed that D2 receptor was 17-fold more sensitive in mGluR3 knockout striate homogenates compared with control. There is also a possibility that D2 receptor hypersensitivity may cause hyper locomotor activity of mGluR3 mice in this study.…”
Section: Discussionmentioning
confidence: 93%
“…This possibility has also been supported by in vitro and in vivo experimental evidence in which group II mGluRs negatively modulated dopamine release in the limbic and cortical regions [5]. Seeman et al [32] revealed that D2 receptor was 17-fold more sensitive in mGluR3 knockout striate homogenates compared with control. There is also a possibility that D2 receptor hypersensitivity may cause hyper locomotor activity of mGluR3 mice in this study.…”
Section: Discussionmentioning
confidence: 93%
“…One relevant finding in the mGlu2 −/− mice is that despite no changes in striatal tissue levels of dopamine (current data and [7]) and no baseline dialysate changes in glutamate or dopamine [7], these mice exhibit enhancement of cocaine-induced extracellular dopamine and glutamate in the NAc [7]. There is also evidence that a greater proportion of dopamine D2 receptors are in a high-affinity state in mGlu2 −/− and mGlu3 −/− mice, which may be indicative of a subtle difference in dopaminergic function [31]. By the same token, the unchanged baseline levels of noradrenaline, 5-HT and cortical dopamine in mGlu2/3 −/− mice reported here do not preclude the occurrence of functionally significant alterations in monoamine signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that combined, sub-effective doses of the mGlu2/3 agonist (1S,2R,5R,6R)-2-amino-4- oxabicyclo[3.1.0]hexane-2,6-dicarboxylic acid (LY379268) and the 5HT2A receptor antagonist, (R)-(+)-α-(2,3-Dimethoxyphenyl)-1-[2-(4-fluorophenyl)ethyl]-4-piperidinemethanol (M100907), are efficacious in an animal model predictive of antipsychotic activity (Uslaner et al 2009a). Other intriguing associations with group II mGluRs have been discovered that are relevant to current models of schizophrenia including the upregulation of high-affinity D2 dopamine receptors in the striatum of mGlu 2 and mGlu 3 knockout mice (Seeman et al 2009). Observations such as these warrant further investigation and should be kept in mind when considering a possible multi-target approach for treatment of psychosis (Wong et al 2010).…”
Section: Group II Mglu Receptors As Therapeutic Targets For Schizomentioning
confidence: 99%